Learning from interorganizational projects - Iftikhar, Rehab; Ahola, Tuomas; Butt, Aurangzeab (Emerald, 2022)
Purpose The purpose of this study is to consolidate the existing research on interorganizational projects and to explore how organizations learn by closely examining multilevel learning, that is, organizational and interorganizational learning. Design/methodology/approach This article adopts a single case study approach, examining the Islamabad–Rawalpindi Metro project in Pakistan, with data consisting of interview results and archival data. An inductive approach is used for data analysis. Findings An empirically grounded learning model was developed based on an interorganizational project following eight lessons: capacity building, personality traits of leadership, working procedures, impeccable planning and implementation, involvement of stakeholders, design compatibility, investigation of underground services, conditions and maintenance of databases, and conceive rational timelines. These lessons learned were classified into three categories: (1) organizational capacity, (2) organizational embeddedness and (3) collective awareness. Originality/value This paper develops a novel learning model that can deepen our understanding of the practices and processes involved in multilevel learning. This study contributes to and extends the literature on organizational and interorganizational learning by studying an interorganizational setting.
Keywords: Interorganizational learning; Interorganizational projects; Lessons learned; Organizational learning; fi=Tuotantotalous|en=Industrial Management|